Archipelagic genetics in a widespread Caribbean anole (2017)
Aim We examine the influence of fluctuating sea levels in a land?bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole (Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad?scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non?equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long?term persistence in the region and periods of population spatial expansion.